2020
DOI: 10.1128/jb.00156-20
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Interfere with the DNA Binding Activity of the Virulence Regulator PrfA of Listeria monocytogenes

Abstract: ABSTRACT Naturally occurring free fatty acids (FFAs) are recognized as potent antimicrobial agents that also affect the production of virulence factors in bacterial pathogens. In the foodborne pathogen Listeria monocytogenes, some medium- and long-chain FFAs act as antimicrobial agents as well as signaling compounds, causing a repression of transcription of virulence genes. We previously observed that the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 52 publications
(93 reference statements)
1
28
0
Order By: Relevance
“…monocytogenes has also been found inside large, single-membrane vacuoles in splenic macrophages of immune-competent mice [ 34 ], suggesting that at least a subset of bacteria might assume an intravacuolar state, be it temporary or prolonged, within an immune-competent host. This scenario seems conceivable given the heterogeneity of intracellular bacterial fate upon infection [ 22 ] and recent insights that PrfA activity is regulated by peptides derived from nutritional sources as well as free fatty acids [ 14 , 35 ]. Nevertheless, whether Listeria -residence vacuoles in vivo resemble any of the vacuolar compartments defined in in vitro studies remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes has also been found inside large, single-membrane vacuoles in splenic macrophages of immune-competent mice [ 34 ], suggesting that at least a subset of bacteria might assume an intravacuolar state, be it temporary or prolonged, within an immune-competent host. This scenario seems conceivable given the heterogeneity of intracellular bacterial fate upon infection [ 22 ] and recent insights that PrfA activity is regulated by peptides derived from nutritional sources as well as free fatty acids [ 14 , 35 ]. Nevertheless, whether Listeria -residence vacuoles in vivo resemble any of the vacuolar compartments defined in in vitro studies remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, antimicrobial medium- and long-chain free fatty acids (FFAs) prevent the expression of PrfA-dependent genes, a repression that can overcome the effect of a mid-level constitutively active EGD G155S- prfA ∗ mutant ( Lillebæk et al, 2017 ). The repressor mechanism occurs by free fatty acids interfering with the DNA binding activity of PrfA ( Dos Santos et al, 2020 ). Similarly, our studies showed that the chitin polymer repressed PrfA-dependent expression in both a WT strain and a G155S- prfA ∗ mutant and suggest that a post-translational modification of PrfA ∗ may inhibit the activity of the protein in CDM.…”
Section: Discussionmentioning
confidence: 99%
“…In Listeria monocytogenes, this includes regulatory targets of the master regulatory protein PrfA (Sternkopf Lillebaek et al, 2017) since free fatty acids alter the expression of PrfA-dependent genes (Sternkopf Lillebaek et al, 2017). Recently, it was shown that free fatty acids can prevent activated PrfA from binding DNA (Dos Santos et al, 2020). This data suggest that fatty acids could prevent other regulatory proteins such as SaeR from binding DNA.…”
Section: Our Data Indicate That Fatty Acids Not Commonly Found Inmentioning
confidence: 99%